A morphologic and crystallographic comparison of CV chondrite matrices. (29th August 2019) - Forman, L. V.; Timms, N. E.; Bland, P. A.; Daly, L.; Benedix, G. K.; Trimby, P. W.
Abstract: Meteoritic matrices are commonly classified by their modal mineralogy, alteration, and shock levels. Other "textural" characteristics are not generally considered in classification schemes, yet could carry important information about their genesis and evolution. Terrestrial rocks are routinely described by grain morphology, which has led to morphology‐driven classifications, and identification of controlling processes. This paper investigates three CV chondrites—Allende (CV3.2oxA ), Kaba (CV3.0oxB ), and Vigarano (CV3.3red )—to determine the morphologic signature of olivine matrix grains. 2D grain size and shape, and crystallographic preferred orientations (CPOs) are quantified via electron backscatter diffraction mapping. Allende contains the largest and most elongate olivine grains, while Vigarano contains the least elongate, and Kaba contains the smallest grains. Weak but notable CPOs exist in some regions proximal to chondrules and one region distal to chondrules, and CPO geometries reveal a weak flattening of the matrix grains against the edge of chondrules within Allende. Kaba contains the least plastically deformed grains, and Allende contains the most plastically deformed grains. We tentatively infer that morphology is controlled by the characteristics of the available population of accreting grains, and aqueous and thermal alteration of the parent body. The extent of overall finite deformation is likely dictated by the location of the sample with respect to compression, the localized environment of the matrix with respect to surrounding material, and the post deformation temperature to induce grain annealing. Our systematic, quantitative process for characterizing meteorite matrices has the potential to provide a framework for comparison within and across meteorite classes, to help resolve how parent body processing differed across and between chondritic asteroids.